Meningkatkan Kepuasan Kerja: Peran Organisasi Pembelajar dan Beban Karyawan (Studi Empiris Karyawan PT Nutrifood Indonesia Area Sumatera Bagian Selatan) - Safani, Diaz; Santati, Parama; Zunaidah, Zunaidah (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to analyze the influence of learning organization and workload on job satisfaction of PT Nutrifood Indonesia employees in the Southern Sumatra area, and is a quantitative descriptive study. The population in this study consisted of 49 employees of PT Nutrifood Indonesia in the Southern Sumatra area (Sumbagsel), specifically from South Sumatra, Lampung, and Jambi. The sample was taken using a saturated sampling technique, with 49 employees as respondents. This study utilizes primary data collected through a questionnaire. Rooted in Herzberg's Two-Factor Theory, the study results demonstrated that a learning organization has a significant positive effect, and workload has a significant negative impact on the job satisfaction of PT Nutrifood Indonesia employees in the Southern Sumatra area.